2017
DOI: 10.1051/0004-6361/201731249
|View full text |Cite
|
Sign up to set email alerts
|

Seeds of Life in Space (SOLIS)

Abstract: Context. Modern versions of the Miller-Urey experiment claim that formamide (NH 2 CHO) could be the starting point for the formation of metabolic and genetic macromolecules. Intriguingly, formamide is indeed observed in regions forming solar-type stars and in external galaxies. Aims. How NH 2 CHO is formed has been a puzzle for decades: our goal is to contribute to the hotly debated question of whether formamide is mostly formed via gas-phase or grain surface chemistry. Methods. We used the NOrthern Extended M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 46 publications
(78 reference statements)
2
69
1
1
Order By: Relevance
“…In recent years, formamide has been observed in low-mass star formation environments such as shocked regions by protostellar jets (e.g., Codella et al 2017). Protostellar shocks produced by episodic jets of matter propagate at supersonic velocity through dense gas surrounding the star.…”
Section: Astrophysical Context and The Importance Of Temperature-progmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, formamide has been observed in low-mass star formation environments such as shocked regions by protostellar jets (e.g., Codella et al 2017). Protostellar shocks produced by episodic jets of matter propagate at supersonic velocity through dense gas surrounding the star.…”
Section: Astrophysical Context and The Importance Of Temperature-progmentioning
confidence: 99%
“…Protostellar shocks produced by episodic jets of matter propagate at supersonic velocity through dense gas surrounding the star. In these shocked regions, the presence of a large number of molecules is due to mechanical release by gas-grain collisions and grain-grain collisions (López-Sepulcre et al 2019;Codella et al 2017). Aside from protostellar shocks, the other low-mass star for-mation environments where formamide has been detected are hot corinos (Kahane et al 2013;López-Sepulcre et al 2015;Marcelino et al 2018;Imai et al 2016;Oya et al 2017;Lee et al 2017).…”
Section: Astrophysical Context and The Importance Of Temperature-progmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, interferometry is the way to image the small (down to ∼ 1 ) regions chemically enriched due to the passage of a shock. In this context, a large number of studies have revealed bow shocks and cavities opened by protostellar jets (Gueth et al 1998;Bachiller et al 1998;Benedettini et al 2007Benedettini et al , 2013Codella et al 2009Codella et al , 2017Persson et al 2012;Santangelo et al 2015;Lefèvre et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Atacama Large Millimeter/submillimeter Array (ALMA) observations by Coutens et al (2016) of IRAS 16293-2422 show that the deuterium fractions in HNCO and NH 2 CHO are very similar, implying a chemical link. On the other hand, Codella et al (2017) observed a shock near L1157-B1 using interferometric observations. Through these observations and follow-up chemical modeling, they concluded that NH 2 CHO is made efficiently in the gas phase from H 2 CO, at least in this source.…”
Section: Introductionmentioning
confidence: 99%